Mengukur Kompetensi Strategis Mahasiswa PIAUD: Analisis SWOT Berbantu ChatGPT pada Matakuliah Manajemen Pendidikan - Vicky Rizki Febrian; Ramza Husmen; Annisaul Khairat (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2026)
Although the development of information and communication technology, particularly Artificial Intelligence (AI) such as ChatGPT, has had a significant impact on the field of education, studies on its use in learning SWOT analysis in the Educational Management course still need to be developed more systematically. This study aims to explore the use of ChatGPT in the SWOT analysis learning process in the Educational Management course. This study used a mixed-methods approach to examine the effectiveness of ChatGPT in helping students understand and analyze SWOT indicators in greater depth. The results show that ChatGPT is an effective and easily accessible digital tool that can support students in identifying and understanding the elements of strengths, weaknesses, opportunities, and threats in the context of SWOT analysis. ChatGPT was also considered capable of explaining concepts, providing applied examples, and encouraging the development of students’ critical thinking. The conclusion of this study affirms that ChatGPT has the potential to serve as an adaptive and innovative learning medium in supporting Educational Management learning. These findings imply the importance of integrating AI technology into learning design to improve the quality of learning that is more interactive, contextual, and relevant to the needs of digital education.